2016
DOI: 10.3354/dao02962
|View full text |Cite
|
Sign up to set email alerts
|

Plant characteristics associated with widespread variation in eelgrass wasting disease

Abstract: Seagrasses are ecosystem engineers of essential marine habitat. Their populations are rapidly declining worldwide. One potential cause of seagrass population declines is wasting disease, which is caused by opportunistic pathogens in the genus Labyrinthula. While infection with these pathogens is common in seagrasses, theory suggests that disease only occurs when environmental stressors cause immunosuppression of the host. Recent evidence suggests that host factors may also contribute to disease caused by oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 51 publications
7
61
0
1
Order By: Relevance
“…To our knowledge, few other re gions have shown equally high prevalence of lesions in Z. marina during recent years. Lesion prevalence has previously been found to vary be tween 0 and 95% (x -= 23%) in Z. marina meadows in northern Europe (Bockelmann et al 2013), and between 6 and 79% (x -= 44%) in the San Juan archipelago, USA (Groner et al 2014(Groner et al , 2016. The prevalence of L. zosterae cells in Z. marina is also higher in our study compared to the few areas where this has previously been measured.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…To our knowledge, few other re gions have shown equally high prevalence of lesions in Z. marina during recent years. Lesion prevalence has previously been found to vary be tween 0 and 95% (x -= 23%) in Z. marina meadows in northern Europe (Bockelmann et al 2013), and between 6 and 79% (x -= 44%) in the San Juan archipelago, USA (Groner et al 2014(Groner et al , 2016. The prevalence of L. zosterae cells in Z. marina is also higher in our study compared to the few areas where this has previously been measured.…”
Section: Discussionsupporting
confidence: 60%
“…No significant difference in L. zosterae infection was found between the 3 high-salinity meadows, but a significant small-scale variation among shoots within meadows was detected. Overall, our results show that high-salinity meadows of Z. marina from the study area have high prevalence of L. zosterae infection compared to what has been reported from other regions (Bockelmann et al 2013, Groner et al 2016. We found that 87 to 100% of the shoots had lesions and that 61 to 91% carried L. zosterae cells.…”
Section: Discussionmentioning
confidence: 36%
See 1 more Smart Citation
“…The ranges of EWD severity observed in phase I (natural infection) are typical of those observed at sites in the San Juan Archipelago during the summer (which our experimental conditions mimicked, Groner et al 2014Groner et al , 2016. It is unclear whether the host, the pathogen or both are driving this shift.…”
Section: Discussionmentioning
confidence: 59%
“…This site was chosen because it has a relatively low EWD prevalence for this region (mean AE SE: 19 AE 3% diseased on 9 August 2014; Groner et al 2016) and a stable eelgrass population has existed since at least 2010 (Wyllie-Echeverria et al 2010, Groner et al 2014, 2016. This site was chosen because it has a relatively low EWD prevalence for this region (mean AE SE: 19 AE 3% diseased on 9 August 2014; Groner et al 2016) and a stable eelgrass population has existed since at least 2010 (Wyllie-Echeverria et al 2010, Groner et al 2014, 2016.…”
Section: Specimensmentioning
confidence: 99%